Neural Networks for Applied Sciences and Engineering: From Fundamentals to Complex Pattern Recognition - Samarasinghe, Sandhya (CRC Press, 2009)
With the large amounts of data collected by scientists and the advent of faster computers, the demand for novel computing methods for analyzing biological and scientific data is growing exponentially. Addressing this need, Neural Networks for Applied Sciences and Engineering: From Fundamentals to Complex Pattern Recognition provides scientists with a simple but systematic introduction to neural networks.